Śrībhāṣyam viṣayānukramaṇī-adhikaraṇasārāvalī-adhikaraṇaviṣaya-adhikaraṇaviṣayavākyaiḥ sahitaḥ (catuḥsūtrībhāgaḥ) - Ramanuja 1077-1157; Ramanuja 1077-1157 (Naī Dillī Bhāratīya Vidyā Prakāśana, 2018)
Commentary on Bādarāyaṇa's Brahmasūtra, basic work of the Vedanta school in Hindu philosophy; Viśiṣṭādvaita viewpoint
Catuḥsūtrībhāgaḥ
Text in Devanagari-Schrift Sanskrit
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Bādarāyaṇa -- Brahmasūtra (Bādarāyaṇa); Vedanta -- Early works to 1800; Viśiṣṭādvaita -- Early works to 1800; Vedanta; Viśiṣṭādvaita; Kommentar